Conservation Theses 2015 - a proposal for the reform of monument protection services - Broda, Aleksander; Konopka, Marek; Landecka, Halina; Zalasińska, Katarzyna; Zielniewicz, Tadeusz (Protection of Cultural Heritage, 2016)
The article explores directions of possible changes to be made to the model of monument protection. It not only recommends specific provisions but also focuses on a model understood as a structure of definitions and relations existing among them. This allows for rough description of a selected aspect of reality. The analysis comes down to deliberations on monument protection system, including necessary duties and competences of government and local government administration bodies. Effects of the principle of subsidiarity and decentralisation of Polish historic preservation administration were brought into special focus. Additionally, narrow scope of duties was determined for state and local government administration bodies.